Vibration Control of Wind Turbines: Recent Advances and Emerging Trends - Fitzgerald, Breiffni; Basu, Biswajit (My University, 2020)
The wind energy sector globally is expanding and developing technically at a rapid pace. Demand for renewable energy is soaring and there is a need for increasing the efficiency and design life of wind turbine structures. The concept of using approaches and techniques developed in the field of structural control for control of wind turbine vibrations is extremely attractive and topical at present. We review the contributions of work on vibration control of wind turbines.We provide an overview on the recent literature focussing on theoretical and experimental work. Passive, semi-active and active control schemes are discussed. The development of bespoke auxiliary damping systems is also discussed as are novel turbine control algorithms utilising existing pitch/generator torque/yaw control hardware
PUBLISHED
Keywords: Wind turbine; Vibration control; Passive control; Active control; Semi-active control; Smart & Sustainable Planet; Wind Energy and Wind Turbines; Wind Energy, General; Wind power; Wind, Wind Energy Engineering